Community Participation in Sand Resource Management in Border Areas: A Case Study of Khorlo Subdistrict, Waeng District, Narathiwat Province - หลีเส็น, อดุลย์; ยะโก๊ะ, แวลาตีฮะ; มะแซ, มูฮัมหมัดรอพรี (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research examines community participation in sand resource management in a border area, using Kholo Subdistrict, Waeng District, Narathiwat Province as a case study. The objectives of this study were: 1) to examine the roles of community participation in sand resource management in Kholo Subdistrict, Waeng District, Narathiwat Province; and 2) to explore guidelines for promoting community participation in sand resource management in the area. This study employed a qualitative research approach. Key informants were selected using purposive sampling based on the objectives of the study. The informants consisted of the Chief Executive of the Subdistrict Administrative Organization, a district officer, community leaders, and local residents, totaling 25 participants. Data were collected through in-depth interviews. The data were analyzed using content analysis by categorizing the information and drawing conclusions through an inductive approach before presenting the findings using descriptive analysis. The results revealed that community participation in sand resource management can be divided into four dimensions: participation in decision-making, participation in implementation, participation in benefit-sharing, and participation in monitoring and evaluation. Most community members mainly participated by receiving information and cooperating with government agencies, while participation in decision-making and monitoring remained relatively limited. Guidelines for promoting community participation consist of five aspects: processes and activities, roles of government and related agencies, community mechanisms and structures, knowledge and communication, and appropriateness to the border area context. Promoting community forums, strengthening participation mechanisms at the community level, and enhancing public understanding of appropriate sand resource utilization can support resource management that is consistent with the local context and lead to long-term sustainability.